Facts and own comments to breast cancer - Zuckermann, Conrado (2015)
Breast cancer is observed both in the multiparous and nulliparous and the absence of sex is not actually protective against this cancer. When it comes to sex, as you know very well, is dominant cancer in women and statistics show us the average figure of 1% in men. The age factor makes us momentarily invade regard to tumor structure, marking the epithelial cancer is predominant after forty and connective earlier age; However, every day we are seeing greater number of epithelial cancers in people between 30 and 40 years.